Analysis of the Effect of Store Image, Service Quality and Price on Customer Loyalty Jesica Fashion Store Medan - Jesica Pratama; Ferry Hidayat; Mario Andriaskiton (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to describe the the Effect of Store Image, Service Quality and Price on Customer Loyalty at Jesica Fashion Store Medan. This research was conducted over 6 (six) months, strating from September 2023 to February 2024. The respondents of this research were constumers at jesica fashion, the number of samples applied in this study was 80 respondents. The instrument used is a questionnaire to collect data from store image variabels, service quality variabels, price variables and loyalty variabels. This research was conducted utilizing validity test, reliability test, descriptive analysis, normality test, multiple linear regression analysis, partial hypothesis test or t test and calculation of the coefficient of determination. The results showed that store image partially had no significant effect while service quality and price had a significant effect on customer loyalty at the jesica fashion store in Medan. And simultaneously store image, service quality and price have a significant effect on customer loyalty jesica fashion medan store. With the value of the coefficient of determination, which is 56.3% and the remaining 43.7% is influenced by other external variables not examined in this study, for example, product innovation, product quality and so on.